1992
DOI: 10.1017/s0031182000074230
|View full text |Cite
|
Sign up to set email alerts
|

Entomopathogenic nematode host finding: response to host contact cues by cruise and ambush foragers

Abstract: SUMMARYSearch behaviour of two entomopathogenic nematode species with different foraging strategies was compared by measuring parameters of unrewarded search after contact with host cues. Steinernema glaseri cruises in search of hosts. Steinernema carpocapsae ambushes hosts. Nematodes should respond to contact with relevant host cues by shifting their search from ranging to localized after contact with them. We predicted that cruising foragers rely on chemical cues more heavily than ambushers. These species we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
115
1
4

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(123 citation statements)
references
References 17 publications
3
115
1
4
Order By: Relevance
“…Cruise foragers also respond to host contact cues. Lewis et al (1992) found that S. glaseri switched to localized search (e.g., speed decreased, distance traveled decreased, proportion of time spent moving decreased) after contact with then removal from host-associated cues (e.g., cuticle, feces). Localized search is thought to maximize the chance that a searcher will either remain in a potentially proWtable patch or reestablish contact with a host that was lost.…”
Section: Interaction Between Foraging Strategy and Hostassociated Cuesmentioning
confidence: 96%
See 1 more Smart Citation
“…Cruise foragers also respond to host contact cues. Lewis et al (1992) found that S. glaseri switched to localized search (e.g., speed decreased, distance traveled decreased, proportion of time spent moving decreased) after contact with then removal from host-associated cues (e.g., cuticle, feces). Localized search is thought to maximize the chance that a searcher will either remain in a potentially proWtable patch or reestablish contact with a host that was lost.…”
Section: Interaction Between Foraging Strategy and Hostassociated Cuesmentioning
confidence: 96%
“…These behavioral mechanisms are consistent with the responses of a diverse range of cruise type foragers (Bell, 1991). Cruise foraging entomopathogenic nematode IJs move using relatively linear movement patterns that are typical of ranging search in the absence of host-associated cues (Lewis et al, 1992). Ranging movement is thought to maximize the area searched.…”
Section: Interaction Between Foraging Strategy and Hostassociated Cuesmentioning
confidence: 99%
“…These factors include soil characteristics (e.g., soil texture and moisture) (Kaya, 1990) and the infective juveniles search strategy ("ambush" versus "cruiser") (Lewis et al, 1992;Grewal et al, 1994). Accordingly, the objective of this study is to evaluate the movement of Heterorhabditis amazonensis RSC2 and Steinernema arenarium A11 in search of S. frugiperda.…”
Section: Introductionmentioning
confidence: 99%
“…The present experiment also demonstrated the same morphological change; the later emergence from the cadavers of host insect, the more decreased in body length and width of the IJs. In addition to the above tendency, the decline of infective behaviors such as nictation (6,7,8,12), migration to host cue (7,11,13), penetration (connoted by mortality of host insects), or active dispersal movement (6,10) were accompanied by the delayed emergence. strategy (13).…”
mentioning
confidence: 99%
“…In addition to the above tendency, the decline of infective behaviors such as nictation (6,7,8,12), migration to host cue (7,11,13), penetration (connoted by mortality of host insects), or active dispersal movement (6,10) were accompanied by the delayed emergence. strategy (13). As has been demonstrated, high nictation rates gave rise to high infectivity of the IJs (6, 12) through high migration and penetration rates (7 , 8).…”
mentioning
confidence: 99%